Efficient Extraction of Synovial Chondromatosis Utilizing the Loose Body Vacuum - Jesus E. Cervantes BS; Eric Hu BS; Stephanie A. Boden MD; Shane J. Nho MD, MS (Video Journal of Sports Medicine)
Background: Synovial chondromatosis is a benign proliferation of the synovial membranes surrounding joints and tendon sheaths that may cause serious joint instability and dysfunction. If left untreated, loose bodies generated within the joint can lead to accelerated joint destruction. Arthroscopic synovectomy with loose body removal has been recommended in certain cases to limit the rate of recurrence. Past techniques have utilized suction as well as manual removal of larger loose bodies. Indications: The patient had extensive right hip synovial chondromatosis as well as femoral acetabular impingement and a labral tear. Thus, she was indicated to receive arthroscopic labral repair along with a femoroplasty and removal of foreign bodies to return functionality and prevent future joint damage. Technique Description: This technique uses a large 5.5-mm bur with the inner bur piece removed from its sleeve. Usage of the sleeve as a vacuum for suctioning small and large loose bodies allows for the minimization of manual removal and soft tissue disruption. Results: Arthroscopic bur sleeves allowed for efficient removal of loose bodies in the setting of synovectomy and symptomatic synovial chondromatosis. Discussion/Conclusion: For this case, removal of synovial chondromatosis utilizing the loose body vacuum resulted in good clearance of larger loose bodies while minimizing soft tissue disruption. Utilization of the same instrument for both arthroscopic debridement and loose body removal is both efficient and cost-effective. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.